Students’ perception of Project-based Learning at IT in Education Course - Nur Tsani, M. Happy; Wulandari, Yasinta; Ainuranti, Asfi (Faculty of Education Universitas Nahdlatul Ulama Yogyakarta, 2026)
This research aims to describe the students’ perceptions towards the implementation of Project-based Learning in IT in Education Class of English Language Education Study Program of Universitas Nahdlatul Ulama Purwokerto. This research used descriptive quantitative method to provide a systematic overview os students ‘responses to the applied learning approach. The data were collected through a questionnaire distributed to fourth semester students using Google Forms. The questionnaire covered several aspects, including students’ perception of the learning materials, the implementation of Project Based Learning in teaching and learning process and the roles of teacher in Project Based Learning. The result shows that 60,5% of students agreed that the teaching material was easy to understand, and 50% of students agreed that Project Based Learning improved their IT skills and Motivation. Related to the role of teacher, there were 44,7% of students perceived that the teacher played an active role in completing the assigned project. Furthermore, to strengthen the quantitative finding, interviews were also conducted as supporting data, and the result were consistent with the main finding og the study. Overall, the findings indicate that most students have positive perception of the implementation of PjBL in the IT in education course. This study highlights that PjBL is an essential and effective teaching; method that enhance students’ motivation. Skils, and engagement. Therefore, the implementation of PjBL is recommended to be continuously developed to support more interactive and meaningful learning experiences.